Control de activos fijos, en el departamento financiero del MIDUVI Babahoyo, durante el año 2020. - Sánchez Sánchez, Roxana Mariela (2022)
The control of fixed assets is a necessary and essential aspect within any organization, for which this must be carried out properly following the parameters and established norms, it is for these reasons and in view of the problems related to the control of fixed assets present in the MIDUVI Babahoyo, that this case study has the objective of analyzing the control of fixed assets, in the financial department of MIDUVI Babahoyo, during the year 2020. As a result of the topic discussed, aspects such as the actions related to the control of fixed assets that were carried out and those that were not during the 2020 period will be presented, as well as the regulations applicable to the management of the aforementioned assets, being these aspects mentioned in the development and conclusions of this case study.